Characterization of the Polish Primitive Horse (Konik) maternal lines using mitochondrial D-loop sequence variation - Jakub Cieslak; Lukasz Wodas; Alicja Borowska; Ernest G. Cothran; Anas M. Khanshour; Mariusz Mackowski (PeerJ, 2017)
The Polish Primitive Horse (PPH, Konik) is a Polish native horse breed managed through a conservation program mainly due to its characteristic phenotype of a primitive horse. One of the most important goals of PPH breeding strategy is the preservation and equal development of all existing maternal lines. However, until now there was no investigation into the real genetic diversity of 16 recognized PPH dam lines using mtDNA sequence variation. Herein, we describe the phylogenetic relationships between the PPH maternal lines based upon partial mtDNA D-loop sequencing of 173 individuals. Altogether, 19 mtDNA haplotypes were detected in the PPH population. Five haplotypes were putatively novel while the remaining 14 showed the 100% homology with sequences deposited in the GenBank database, represented by both modern and primitive horse breeds. Generally, comparisons found the haplotypes conformed to 10 different recognized mtDNA haplogroups (A, B, E, G, J, M, N, P, Q and R). A multi-breed analysis has indicated the phylogenetic similarity of PPH and other indigenous horse breeds derived from various geographical regions (e.g., Iberian Peninsula, Eastern Europe and Siberia) which may support the hypothesis that within the PPH breed numerous ancestral haplotypes (found all over the world) are still present. Only in the case of five maternal lines (Bona, Dzina I, Geneza, Popielica and Zaza) was the segregation of one specific mtDNA haplotype observed. The 11 remaining lines showed a higher degree of mtDNA haplotype variability (2–5 haplotypes segregating in each line). This study has revealed relatively high maternal genetic diversity in the small, indigenous PPH breed (19 haplotypes, overall HapD = 0.92). However, only some traditionally distinguished maternal lines can be treated as genetically pure. The rest show evidence of numerous mistakes recorded in the official PPH pedigrees. This study has proved the importance of maternal genetic diversity monitoring based upon the application of molecular mtDNA markers and can be useful for proper management of the PPH conservation program in the future.